Simultaneous implementation of resistive switching and rectifying effects in a metal-organic framework with switched hydrogen bond pathway - Yao, Zizhu (2020)
Resistive random-access memory (RRAM) has evolved as one of the most promising candidates for the next-generation memory, but bistability for information storage, simultaneous implementation of resistive switching and rectification effects, and a better understanding of switching mechanism are still challenging in this field. Herein, we report a RRAM device based on a chiral metal-organic framework (MOF) FJU-23-H2O with switched hydrogen bond pathway within its channels, exhibiting an ultralow set voltage (~0.2 V), a high ON/OFF ratio (~105), and a high rectification ratio (~105). It is not only the first MOF with voltage-gated proton conduction but also the first single material showing both rectifying and resistive switching effects. By single-crystal x-ray diffraction analyses, the mechanism of the resistive switching has been demonstrated.